2022
DOI: 10.1542/peds.2022-056415l
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Neurodevelopmental Outcomes in Neonates With Congenital Heart Disease

Abstract: Neurodevelopmental impairment is a common and important long-term morbidity among infants with congenital heart disease (CHD). More than half of those with complex CHD will demonstrate some form of neurodevelopmental, neurocognitive, and/or psychosocial dysfunction requiring specialized care and impacting long-term quality of life. Preventing brain injury and treating long-term neurologic sequelae in this high-risk clinical population is imperative for improving neurodevelopmental and psychosocial outcomes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 196 publications
1
6
0
Order By: Relevance
“…Neonates and infants with critical congenital heart disease are at risk for a number of postnatal complications, including growth failure, feeding and breastfeeding challenges, and necrotizing enterocolitis [24][25][26][27][28]. They are also known to be at risk for neurodevelopmental impairments [29,30]. Ongoing SSC in an intensive care setting can be challenging, and many parents have expressed fears around holding their infant in the ICU as well as significant stress throughout the ICU stay [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Neonates and infants with critical congenital heart disease are at risk for a number of postnatal complications, including growth failure, feeding and breastfeeding challenges, and necrotizing enterocolitis [24][25][26][27][28]. They are also known to be at risk for neurodevelopmental impairments [29,30]. Ongoing SSC in an intensive care setting can be challenging, and many parents have expressed fears around holding their infant in the ICU as well as significant stress throughout the ICU stay [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…While research into improving current diagnostic, prognostic and treatment options for NDD in CHD is on-going, there are a number of practical ways in which neurodevelopmental outcomes can be maximised for the CHD patient ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Predominant lesions include patterns of white matter injury and stroke; the prevalence and severity of which are typically worse in infants with univentricular lesions ( 65 , 68 ). Recently, Peyvandi and colleagues found that moderate to severe peri-operative injury is associated with subsequent reduced brain growth ( 68 ), demonstrating a complex interplay between brain development and acquired injury and a possible “two-hit phenomena” ( 69 ).…”
Section: Brain Structure and Function: Insights From Neuroimagingmentioning
confidence: 99%
“…These strategies can include promoting parent-child bonding with kangaroo care or music therapy, reducing noise and implementing cycled lighting to maintain the circadian rhythm. 40…”
Section: Discussionmentioning
confidence: 99%